Modulating Neurological Complications of Emerging Infectious Diseases: Mechanistic Approaches to Candidate Phytochemicals - Fakhri, Sajad; Mohammadi Pour, Pardis; Piri, Sana; Farzaei, Mohammad Hosein; Echeverría, Javier (Frontiers in Pharmacology, 2021)
Growing studies are revealing the critical manifestations of Influenza, Dengue virus infection, Zika virus disease, and Ebola, as emerging infectious diseases. However, their corresponding mechanisms of major complications headed for neuronal dysfunction are not completely understood. From the mechanistic point of view, during emerging infectious diseases, inflammatory/oxidative mediators are activated towards a less cell migration, neurogenesis impairment, and neuronal death. Accordingly, the virus life cycle and associated enzymes, as well as host receptors, cytokine storm, and multiple signaling mediators are the main players of emerging infectious diseases. Consequently, chemokines, interleukins, interferons, carbohydrate molecules, toll-like receptors, and tyrosine kinases (e.g., TAM), are leading orchestrates of peripheral and central complications which are in a near interconnection. Of resulted neuronal manifestations, inflammatory polyneuropathy, encephalopathy, meningitis, myelitis, stroke, Guillain-Barré syndrome, radiculomyelitis, meningoencephalitis, memory loss, headaches, cranial nerve abnormalities, tremor, and seizure have attracted much attention. The complex pathophysiological mechanism behind the aforementioned complications urges the need for finding multi-target agents with higher efficacy and lower side effects. In recent decades, the natural kingdom has been highlighted as promising neuroprotective natural products through modulating several dysregulated signaling pathways/mediators. In the present study, neuronal manifestations of some emerging infectious diseases, and underlying pathophysiological mechanisms are provided. Besides, a mechanistic-based strategy is developed to introduce candidate natural products as promising multi-target agents in combating major dysregulated pathways towards neuroprotection in Influenza, Dengue virus infection, Zika virus disease, and Ebola.